Nietzsche’s Übermensch as a Metaphor for Education - Fitzsimons, Peter (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
Rather than appealing to universal truth or morality based on the power of reason, Nietzsche’s impassioned plea for resuscitating the embodied self as a source of ethics provides a new perspective on educational philosophy. Within the concept of Will to Power, he offers the notion of the Übermensch as a model for overcoming the social limitations of Christian morality and the dictates of fashion. In a formative state, ‘untimely men’ (and here, read ‘Nietzsche’) stand outside the homogenising influence of the State. Nietzsche’s Übermensch, involving a continuous process of ‘overcoming’ and ‘becoming’, is suggested as an alternative to the autonomous liberal subject as an educational ideal. It provides a perspective that contrasts with the egalitarian and collectivist notions that underpin social democracy and social justice as guiding ideals for educational endeavour. This paper questions the liberal hope that education is automatically the path to freedom and autonomy, arguing that education can be valued as a means of developing a reflective or critical view on our social predicament. Übermensch, perhaps the closest Nietzsche comes to an educational ideal, represents agonistic engagement with our social predicament and an overcoming of instrumental views about education. This paper investigates Nietzsche’s figure of the Übermensch and examines some functional aspects of that same figure that help to explain the notion of education relevant to this paper.